1 - Itinéraires et terroirs du Sahel : la poussée méridionale de longue durée dans le peuplement de l’Afrique de l’Ouest - Mamadou Fall (Afrika Zamani, 2022)
From the Adrar in the southern edge of the Sahara to the Rio Grande in the Mandingo settlements in the Atlantic shore, this paper emphasizes the role Fulbe, Soninke, Berber and Mandingo migrations and settlements played in the formation of West Africa. Pre-modern and post-colonial transformations in African society gain therefore a major role in space configuration and indigenous collective identities beco ing part of modern universalism, nation building and development processes.